Exceptional diazoxide sensitivity in hyperinsulinaemic hypoglycaemia due to a novel HNF4A mutation. (16th May 2019) - Arya, Ved Bhushan; Kalitsi, Jennifer; Hickey, Ann; Flanagan, Sarah E; Kapoor, Ritika R
Summary: Diazoxide is the first-line treatment for patients with hyperinsulinaemic hypoglycaemia (HH). Approximately 50% of patients with HH are diazoxide resistant. However, marked diazoxide sensitivity resulting in severe hyperglycaemia is extremely uncommon and not reported previously in the context of HH due to HNF4A mutation. We report a novel observation of exceptional diazoxide sensitivity in a patient with HH due to HNF4A mutation. A female infant presented with severe persistent neonatal hypoglycaemia and was diagnosed with HH. Standard doses of diazoxide (5 mg/kg/day) resulted in marked hyperglycaemia (maximum blood glucose 21.6 mmol/L) necessitating discontinuation of diazoxide. Lower dose of diazoxide (1.5 mg/kg/day) successfully controlled HH in the proband, which was subsequently confirmed to be due to a novel HNF4A mutation. At 3 years of age, the patient maintains age appropriate fasting tolerance on low dose diazoxide (1.8 mg/kg/day) and has normal development. Diagnosis in proband's mother and maternal aunt, both of whom carried HNF4A mutation and had been diagnosed with presumed type 1 and type 2 diabetes mellitus, respectively, was revised to maturity-onset diabetes of young (MODY). Proband's 5-year-old maternal cousin, also carrier of HNF4A mutation, had transient neonatal hypoglycaemia. To conclude, patients with HH due to HNF4A mutation may require lower diazoxide than other group of patients with HH. Educating the families about the risk of marked hyperglycaemia with diazoxide is essential. The clinical phenotype of HNF4A mutation can be extremely variable. Learning points: Awareness of risk of severe hyperglycaemia with diazoxide is important and patients/families should be accordingly educated. Some patients with HH due to HNF4A mutations may require lower than standard doses of diazoxide. The clinical phenotype of HNF4A mutation can be extremely variable.